2017
DOI: 10.1186/s12885-017-3285-6
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein-D predicts prognosis of interstitial lung disease induced by anticancer agents in advanced lung cancer: a case control study

Abstract: BackgroundInterstitial lung diseases induced by anticancer agents (ILD-AA) are rare adverse effects of anticancer therapy. However, prognostic biomarkers for ILD-AA have not been identified in patients with advanced lung cancer. Our aim was to analyze the association between serum biomarkers sialylated carbohydrate antigen Krebs von den Lungen-6 (KL-6) and surfactant protein D (SP-D), and clinical characteristics in patients diagnosed with ILD-AA.MethodsBetween April 2011 and March 2016, 1224 advanced lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…A prospective study of 42 patients with DIILD undergoing transbronchial lung biopsy (TBLB) or bronchoalveolar lavage (BAL) reported an overall diagnostic agreement of 67% [ 15 ], while a retrospective analysis of patients with DIILD undergoing TBLB ( n = 4) or open biopsy ( n = 16) at a single centre reported a lower diagnostic agreement (45%) [ 119 ]. In contrast, CT features of diffuse alveolar damage (DAD) are highly congruous with histopathological features of DAD [ 1 ] and confer high mortality [ 33 , 39 , 80 , 90 , 94 , 95 , 121 , 122 ]. In general, the correlation imaging pattern of CT and pathology is suboptimal [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study of 42 patients with DIILD undergoing transbronchial lung biopsy (TBLB) or bronchoalveolar lavage (BAL) reported an overall diagnostic agreement of 67% [ 15 ], while a retrospective analysis of patients with DIILD undergoing TBLB ( n = 4) or open biopsy ( n = 16) at a single centre reported a lower diagnostic agreement (45%) [ 119 ]. In contrast, CT features of diffuse alveolar damage (DAD) are highly congruous with histopathological features of DAD [ 1 ] and confer high mortality [ 33 , 39 , 80 , 90 , 94 , 95 , 121 , 122 ]. In general, the correlation imaging pattern of CT and pathology is suboptimal [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other: For BAL, the presence of desquamated type II pneumocytes is associated with mortality [ 16 ]. Others have also found that circulating and/or BAL KL-6 and heat shock protein 47 are associated with higher mortality [ 12 , 119 , 121 , 122 ]. Their association with a more severe clinical presentation and with DAD, however, means that their incremental value as prognostic markers remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Inversely, SFTPB and SFTPC are hydrophobic proteins with the capacity of mitigating surface tension in the lung [12]. Strikingly, it has been proposed that SFTPD expression was associated with tumour progression and survival of patients with lung cancer [13][14][15]. Furthermore, recent evidence also showed that SFTPD could suppress the progression of pancreatic cancer by inducing epithelial-mesenchymal-transition (EMT) and apoptosis of pancreatic cancer cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a similar predictive role of Surfactant Protein D (SP-D) for onset of ILD induced by anticancer agents was compared with KL 6 in an interesting case control study [18]. Nakamura et al also reported that SP-D was associated with worse prognosis and development of diffuse alveolar damage [18].…”
Section: Casementioning
confidence: 99%
“…KL 6 is typically elevated in patients with idiopathic interstitial pneumonia and in certain cases of cancer, and may therefore be useful for evaluating disease activity and clinical outcome in patients with ILD-IPF: it could predict the likelihood of radiation pneumonitis or lung toxicity induced by chemotherapy [15][16][17][18][19][20]. Recently, a similar predictive role of Surfactant Protein D (SP-D) for onset of ILD induced by anticancer agents was compared with KL 6 in an interesting case control study [18]. Nakamura et al also reported that SP-D was associated with worse prognosis and development of diffuse alveolar damage [18].…”
Section: Casementioning
confidence: 99%